Technologies proposed for nursing work: an integrative review (Research, Society and Development, 2022)
Through an integrative literature review, we sought to identify the technologies proposed for nursing work and analyze possible changes in the work of this professional category. The articles were selected from the Nursing Database. The sample consisted of 42 articles that met the objectives of the study. The innovations were classified by area of teaching/learning, care and management and most of them are aimed at teaching nursing techniques. Among the benefits provided, care innovation and the possibility of care qualification stand out. However, contradictorily, in the capitalist mode of production, nursing work can suffer impacts such as unemployment, underemployment and precariousness of working conditions and bonds. Reflecting on the possible impacts of the insertion of new technologies in nursing work allows not only to show the reality of these workers and the future challenges of the profession, but also to rethink care.